Planning, procurement and quality management (Thomas Telford, 1993)
This document sets out technical and procedural recommendations covering: the site investigation and its objectives; planning and design of the investigation and methods of reporting; the quality management of the investigation; and the relationships between the parties involved.
Keywords: Structural engineering -- Management.; Structural engineering -- Materials management.; Structural engineering -- Quality control.; elektronické knihy; electronic books